Real-time implementation of a multivariable sliding mode nonlinear position control system - Rojas Moreno, Arturo (2005)
This research work deals with the real-time implementation of a nonlinear multivariable position control system which uses a sliding mode controller to generate the control forces. Such a control forces will be applied to  translational robot arm of 2 degrees of freedom that consist of a cart mounted on a pair of rails and a link mounted on a pivot point located on the cart. The cart and the link (the arm of the robot) are driven by DC servomotors. Experimentalresults obtained from the designed nonlinear control system will demonstrate that the designed control inputs applied on the servomotors make the outputs (sliding motion of the cart and angular positions of the arm) capable of tracking arbitrary trajectorie.